2022
DOI: 10.3390/membranes12100924
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenylene Sulfide-Based Membranes: Recent Progress and Future Perspectives

Abstract: As a special engineering plastic, polyphenylene sulfide (PPS) can also be used to prepare membranes for membrane separation processes, adsorption, and catalytic and battery separators because of its unique properties, such as corrosion resistance, and chemical and thermal stability. Nowadays, many researchers have developed various types of PPS membranes, such as the PPS flat membrane, PPS microfiber membrane and PPS hollow fiber membrane, and have even achieved special functional modifications. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…PPS was discovered in 1888 as a byproduct of a chemical reaction and is nowadays industrially synthesized using either the Phillips method (synthesis of linear PPS resin, sodium sulfide method) or the sulfur method, in which dichlorobenzene and sulfur are polycondensed to produce the PPS resin at 175− 250 °C under ambient pressure in polar solvents, such as hexamethylphosphoryltriamide or N-methylpyrrolidone. 33 The three main forms of PPS membranes are flat, hollow fiber and ultrafine fiber membranes. 33 Even though flat PPS membranes have an important research significance and practical application in many fields (oil−water separation, seawater desalination and dye wastewater treatment), shortcomings such as a low module loading density and insufficient mechanical properties affect the practical application of PPS flat membranes in electrolytic processes.…”
Section: Poly(phenylene Sulfide) Feltsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPS was discovered in 1888 as a byproduct of a chemical reaction and is nowadays industrially synthesized using either the Phillips method (synthesis of linear PPS resin, sodium sulfide method) or the sulfur method, in which dichlorobenzene and sulfur are polycondensed to produce the PPS resin at 175− 250 °C under ambient pressure in polar solvents, such as hexamethylphosphoryltriamide or N-methylpyrrolidone. 33 The three main forms of PPS membranes are flat, hollow fiber and ultrafine fiber membranes. 33 Even though flat PPS membranes have an important research significance and practical application in many fields (oil−water separation, seawater desalination and dye wastewater treatment), shortcomings such as a low module loading density and insufficient mechanical properties affect the practical application of PPS flat membranes in electrolytic processes.…”
Section: Poly(phenylene Sulfide) Feltsmentioning
confidence: 99%
“…33 The three main forms of PPS membranes are flat, hollow fiber and ultrafine fiber membranes. 33 Even though flat PPS membranes have an important research significance and practical application in many fields (oil−water separation, seawater desalination and dye wastewater treatment), shortcomings such as a low module loading density and insufficient mechanical properties affect the practical application of PPS flat membranes in electrolytic processes. Development of PPS advanced membranes is challenged by the insolubility of PPS in most solvents and its high melting point.…”
Section: Poly(phenylene Sulfide) Feltsmentioning
confidence: 99%
“…70 It is worth mentioning that, PPS materials also show the great potential of a wide range of separation membrane fields in harsh environments. [71][72][73] Especially for a high concentration of sewage, high temperature tail gas and corrosive solid waste, PPS membranes with high temperature resistance, organic solvent resistance, acid/alkali resistance and oxidation resistance have attracted many researchers and become an valuable research direction. Zhang et al prepared a PPS/oxidized PPS composite membrane which showed good hydrophilicity, chemical and solvent resistance, superior water flux, and anti-fouling performance, which could be applied to high-temperature filter, high-efficiency oil absorption and high-performance lithium-ion battery.…”
Section: Research Improvement and Progressmentioning
confidence: 99%
“…The porous diaphragms (Figure a) are typically prepared from poly­(arylene ether sulfone)-bonded inorganic hydrophilic particles by a phase inversion casting process to form a highly porous composite material with typical pore size at the micrometer scale and with denser surface layers . Poly­(phenylene sulfide) is also used in the form of fibers, but requires alternative processing routes due to the insolubility in organic solvents . The anion-exchange membrane (AEM) approach (Figure b) is based on polymer chemistries equipped with covalently attached cationic functionalities, and membranes derived from quaternary ammonium-functionalized poly­(arylene ether sulfone)­s were among the first AEM chemistries used for electrolysis device tests. , Specific examples of the most successful cationic ionomers or ionenes with demonstrated device performance at the single-cell level so far include structures derived from polystyrene, poly­(arylene benzimidazolium), poly­(arylene piperidinium), poly­(arylene alkylene), and polyphenylene. At the stack level, systems based on polycarbazole membranes have also been reported .…”
mentioning
confidence: 99%
“… 11 Poly(phenylene sulfide) is also used in the form of fibers, but requires alternative processing routes due to the insolubility in organic solvents. 12 The anion-exchange membrane (AEM) approach ( Figure 1 b) is based on polymer chemistries equipped with covalently attached cationic functionalities, and membranes derived from quaternary ammonium-functionalized poly(arylene ether sulfone)s were among the first AEM chemistries used for electrolysis device tests. 13 , 14 Specific examples of the most successful cationic ionomers or ionenes with demonstrated device performance at the single-cell level so far include structures derived from polystyrene, poly(arylene benzimidazolium), poly(arylene piperidinium), poly(arylene alkylene), and polyphenylene.…”
mentioning
confidence: 99%